a ANALYSIS OF CART PRODUCTION EFFICIENCY BAMBOO WOVEN IN BINJAI CITY: ANALYSIS OF TECHNICAL, ALLOCATIVE, ECONOMIC EFFICIENCY OF BAMBOO WOVEN BASKETS USING FRONTIER IN BINJAI CITY - Yolanda, Triyana; Lindawati; Isfenti Sadalia (Universitas Medan Area, 2024)
There are fewer bamboo craftsmen in Binjai City, due to difficulties in continuing their business, the reason being the lack of participation of young people in preserving the bamboo craft business which has been running for quite a long time. The price of raw materials is very high and sometimes fluctuates so that if the price of raw materials is high, plus production costs, the selling price will be very high. So this research aims to analyze technical, price and economic efficiency in the use of production factors in the bamboo woven craft business in Binjai City. This research was conducted using cross section primary data. Data were analyzed using a stochastic frontier production function analysis tool. The research results show that in terms of technical efficiency, all craftsmen are technically efficient because the efficiency index value is more than 0,7. The average value of respondents' technical efficiency is 0,87. This value shows the average achievement of technical efficiency in the woven bamboo basket craft business of 87,64%. This condition shows that on average it still has a chance of 12,36% to achieve maximum efficiency. However, in terms of allocative and economic efficiency, all respondents are not yet efficient because the efficiency index value has not reached more than or equal to 1. The average value of allocative efficiency only reaches 0,26 and 0,22 for economic efficiency, which means that each craftsman requires additional input.